Structure and composition of Cretaceous coal-bearing deposits at Ulziit rift depression margin in East-Gobi region of Mongolia - M. N. Grechukhin; P. A. Ignatov (Известия высших учебных заведений: Геология и разведка)
The paper introduces for the first time the data on the structure and composition of coal-bearing sediments in Ulziit tectonic-sedimentary basin’s margin based on the authors analysis of the core material and borehole geophysical data. The presence of the numerous stereotyped Mesozoic depressions in Mongolia and China related to the intercontinental rift basins defines an actuality of this paper. The authors stress the specific contrast relations of the defined lithogenetic associations. Results by the set of geological and geophysical data correlation analysis illustrate the possibility of local marking horizons definition in the continental sediments of the complexly interlaced strata that has a practical interest for the geological mapping and exploration of the mineral resources in the similar sedimentary basins of Central Asia.